A Survey Study of Spiritual Change and Related Factors Among the Surviving Loved Ones of Homicide Victims. Issue 23 (December 2021) - Johnson, Shannon
A survey study was conducted as the second phase of a sequential mixed-methods study of spiritual change after the homicide of a loved one. The purpose of the study was to test the Theory of Post-Homicide Spiritual Change (Theory of PHSC), which emerged in Phase 1 of the larger study. The formulation of survey research questions and hypotheses was guided by the emerging theory. Data were collected online using Qualtrics. Respondents ( N = 112) completed a demographic and background questionnaire that was devised for the study based on a review of important factors in homicidal bereavement. They also responded to established measures, including a modified version of the Posttraumatic Growth Inventory, the Integration of Stressful Life Experiences Scale (ISLES), and the Perceived Justice Scale. The ISLES was comprised of two subscales—Comprehensibility and Footing in the World. Significant findings revealed that posttraumatic growth (PTG) was higher among those for whom 3 or more years had passed since the murder, as compared with those for whom fewer than 3 years had passed. The age of the victim was positively correlated with integration of loss. Christian respondents reported higher levels of integration of loss and PTG, as compared with non-Christian respondents. Integration of loss was a mediator of the relationship between perceived justice and integration of loss, while footing in the world was a mediator of the relationship between comprehensibility and PTG. Contrary to hypotheses, integration of loss did not differ by time since murder. This finding is interpreted in terms of the limitations of the study sample and in terms of future research directions in this area. The results of this study yield important insight into spiritual change and related factors that can be used to guide service provision with the homicide survivor population.